2017
DOI: 10.1109/tkde.2016.2606098
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-NMF-PCA Unified Framework for Data Clustering

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Image related: Some work embeds graphs constructed from images, and then use the embedding for image classification ( [81], [82]), image clustering [101], image segmentation [154], pattern recognition [80], and so on.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Image related: Some work embeds graphs constructed from images, and then use the embedding for image classification ( [81], [82]), image clustering [101], image segmentation [154], pattern recognition [80], and so on.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Furthermore, we have shown that it was possible to improve the consensus quality through the use of finite mixture models, allowing more powerful underlying settings than cluster-based consensus involving plain similarities or distances. A future work will be to investigate the use of cluster ensembles for other recent clustering algorithms [1][2][3]19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Since the original data matrix in the real world usually contains very complex information, the NMF method based on a one-layer structure is difficult to mine the high-level features of the data [29]. Inspired by recent advances in deep learning, Trigeorgis et al [22] proposed a Deep semi-Nonnegative Matrix Factorization (Deep semi-NMF) algorithm, which can construct a deep network by factorizing the data many times through the semi-NMF method [31], so that the relationships between the different layers can be exploited to reveal the intrinsic high-level features of the original data. The main idea of Deep semi-NMF is to decompose the coding coefficient matrix V several times through the semi-NMF algorithm, and take the decomposed results as the input of the next layer, and finally build a deep network structure.…”
Section: Deep Semi-nonnegative Matrix Factorizationmentioning
confidence: 99%